Ferroptosis in hepatocellular carcinoma, from mechanism to effect - Jiang, Shuang; Zhang, Guangcong; Ma, Yanan; Wu, Dongyu; Xie, Da; Zhou, Songke; Jiang, Xuemei (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) is a prevalent malignant tumor worldwide, characterized by high malignancy and rapid progression. Most cases are diagnosed at intermediate to advanced stages. Current treatment methods have limited efficacy, resulting in high recurrence rates and poor prognosis. Radical hepatectomy remains the primary treatment for HCC, complemented by radiotherapy, chemotherapy, targeted therapy, and immunotherapy. Despite significant improvement in patient prognosis with radical hepatectomy, the five-year survival rate post-surgery remains low; thus necessitating exploration of more effective therapeutic approaches. Ferroptosis is a recently discovered form of cell death that can modulate the occurrence and development of HCC through various mechanisms. This article aims to elucidate the mechanism of ferroptosis and its impact on HCC development to provide novel insights for diagnosis and treatment.